Repair of Disposable Air Filters by Solution-Blown Nano/Micro Fibrous Patches - Lee, Ji Soo; Kim, Hyun Ji; Jung, Seojin; Kim, Jooyoun; Lee, Min Wook (AMER CHEMICAL SOC, 2020)
The material used for disposable air filters is generally made of polypropylene, a typical petroleum compound, and is not easily degradable. As a result, secondary environmental pollution is caused by the massive waste of disposable respirators that are consumed by the world's population. In this study, we manufactured solution-blown fibers with solvents that are nontoxic to the environment and the human body. When the perforated respirators were coated with the solution-blown fibers, the repaired respirators attained the filter performance required by the U.S. National Institute for Occupational Safety and Health (NIOSH) for N95 classification. The application of the solution-blown fibers developed in this study can be used as a facile remedy for the reuse and extension of effective service life for perforated or torn respirators.